Toward a storage ring coherent light source based on an angular dispersion-induced microbunching scheme - Changliang Li; Bocheng Jiang; Chao Feng; Qiang Gu; Zhenghe Bai; Weishi Wan; Qinglei Zhang; Kun Wang (Journal of Synchrotron Radiation)
The combination of reversible angular dispersion-induced microbunching (ADM) and the rapid damping storage ring provides a storage-ring-based light source with the capability to produce longitudinal coherent radiation with a high repetition rate. This paper presents a prototype design for a test facility based on the study by Jiang et al. [Sci. Rep. (2022), 12, 3325]. The modulation–demodulation section is inserted into a long straight section of the storage ring instead of a bypass line, which poses great challenges for the optimization of the nonlinear dynamics of the storage ring. However, this design avoids the challenging injection and extraction system connecting to the bypass line. To utilize mature laser technology and reduce the difficulty of the reversible ADM lattice design, we use a long-wavelength 1030 nm seed laser. In the simulation, we achieved 20th harmonic radiation with a bunching factor of about 7.2%. The growth rate of vertical emittance and energy spread of the electron beam for a single pass are about 11% and 0.02%, respectively. When the energy of the electron beam is 800 MeV and two sets of damping wigglers are employed, the damping time in the vertical plane is reduced to 8.31 ms. This results in a 438 kHz repetition rate of the coherent radiation at the new equilibrium state.